2018
DOI: 10.3390/s18041054
|View full text |Cite
|
Sign up to set email alerts
|

A Distance Boundary with Virtual Nodes for the Weighted Centroid Localization Algorithm

Abstract: In wireless sensor networks, accurate location information is important for precise tracking of targets. In order to satisfy hardware installation cost and localization accuracy requirements, a weighted centroid localization (WCL) algorithm, which is considered a promising localization algorithm, was introduced. In our previous research, we proposed a test node-based WCL algorithm using a distance boundary to improve the localization accuracy in the corner and side areas. The proposed algorithm estimates the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…erefore, the cost of network construction can be reduced by using the algorithm. Hence, the authors proposed a new DV-Hop localization algorithm based on the half-measure weighted centroid [16].…”
Section: Error Analysis For the Dv-hop Algorithmmentioning
confidence: 99%
“…erefore, the cost of network construction can be reduced by using the algorithm. Hence, the authors proposed a new DV-Hop localization algorithm based on the half-measure weighted centroid [16].…”
Section: Error Analysis For the Dv-hop Algorithmmentioning
confidence: 99%
“…In order to improve the localisation accuracy, a weighted CL (WCL) method has been proposed [10, 11] that combines both CL and RSS. WCL improves the accuracy to an extent but we have identified that there exists two major deficiencies: (a) the accuracy deteriorates at the corners and sides of the geometric figure due to the centroid property [12] and (b) the localisation accuracy decreases significantly if an inappropriate node is selected. A number of improved weighted centroid algorithms are thus proposed to improve the localisation accuracy considering the first deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Kaur et al [13] proposed a localisation algorithm using weights that consider the influence of different factors such as the number of anchors, communication radius and nearest anchor to determine the position of the unknown node. While others used virtual concepts [12, 14–16] to improve the localisation accuracy. Kim and Shin [12] proposed a test node‐based WCL algorithm using a distance boundary to improve the localisation accuracy at the corner and side areas.…”
Section: Introductionmentioning
confidence: 99%
“…Underwater sensor networks (UWSNs) play a pivotal role in such studies by providing basic technical support for gathering, organizing, and reporting mission-critical data [7]. Besides some common characteristics between terrestrial and underwater sensor networks, such as large-scale deployment and energy constraints, UWSNs have some differences compared to their terrestrial counterparts [8,9,10]. For instance, unlike terrestrial sensor networks where radio waves are used as a medium of communication, UWSNs use acoustic waves predominantly [11,12].…”
Section: Introductionmentioning
confidence: 99%